Vidas que fazem história no ensino de matemática : as trajetórias de formação profissional e as tecnologias - Silva, Mercedes Matte da (2017)
This research’s objective is to present and analyze the narratives of Math professors in the State of Rio Grande do Sul, which in its whole allow us to understand their thought and pedagogical practice. In their narratives, the professors organized and redid their personal and professional paths under the stimulus of their projects of identity and their relation with technologies. To have the understanding regarding the formation of a Math professor, the starting point was to clarify not only the way the first Math professors of Brazil got their academic formation in the moment they created the universities; but also, point out the origin of this model of professor in this subject. With time, modifications occur with the creation of technologies and its insertion in Math classes. Following a perspective of qualitative research, the methodological proposition “História Oral de Vida” (Oral History of Life), we used interviews with 12 Math professors who have experience teaching undergraduate courses in Math. The narratives allowed visibility in the Math academic field in the period of three generations of professors and the comprehension of technological advancement to learn, teach and think Math.